2019
DOI: 10.1093/nar/gkz1150
|View full text |Cite
|
Sign up to set email alerts
|

Protect-seq: genome-wide profiling of nuclease inaccessible domains reveals physical properties of chromatin

Abstract: In metazoan cell nuclei, heterochromatin constitutes large chromatin domains that are in close contact with the nuclear lamina. These heterochromatin/lamina-associated domains (LADs) domains are difficult to profile and warrants a simpler and direct method. Here we report a new method, Protect-seq, aimed at identifying regions of heterochromatin via resistance to nuclease degradation followed by next-generation sequencing (NGS). We performed Protect-seq on the human colon cancer cell line HCT-116 and observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…For instance, HCT116 colon cancer cells appear to harbor compartmentalization signatures in Hi-C that are distinct from other cell lines (Nichols & Corces, 2021; Xiong & Ma, 2019). Furthermore, using Protect-seq, which measures peripheral heterochromatin, we have previously shown that in HCT116, H3K27me3 and H3K9me3 distinguish between two structurally distinct types of heterochromatin (Spracklin & Pradhan, 2020). Therefore, we sought to identify groups of loci through similarities in long-range interaction profiles (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, HCT116 colon cancer cells appear to harbor compartmentalization signatures in Hi-C that are distinct from other cell lines (Nichols & Corces, 2021; Xiong & Ma, 2019). Furthermore, using Protect-seq, which measures peripheral heterochromatin, we have previously shown that in HCT116, H3K27me3 and H3K9me3 distinguish between two structurally distinct types of heterochromatin (Spracklin & Pradhan, 2020). Therefore, we sought to identify groups of loci through similarities in long-range interaction profiles (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Prompted by these observations, we sought out perturbation systems that disrupt H3K9me3-HP1α/β chromatin. First, the DNMT1 hypomorph and DNMT3b knockout cell line (termed DKO) (Rhee et al, 2002), is a DNA methylation-deficient line derived from HCT116 that has been reported to have defects in H3K9me3 (Lay et al 2015) and HP1α/β deposition (Spracklin & Pradhan, 2020). To investigate acute effects of DNA methylation dysfunction on compartmentalization and chromatin state, we also examined HCT116 cells treated with 5-Azacytidine for 48h (hereafter referred to as 5Aza) ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, ChIP-seq relies on crosslinking and antibodies, which are sources of technical biases and potential issues of sensitivity or cross-reactivity, respectively. More recently proposed high-throughput sequencing methods for genome-wide mapping of LADs and heterochromatin, such as gradient-seq 40,41 and protect-seq 42 , also rely on crosslinking.…”
mentioning
confidence: 99%
“…Other chromatin features are correlated with inaccessible chromatin. Constitutive heterochromatin domains marked by H3K9me3 and H3K27me3 are reported to be largely inaccessible in higher eukaryotes [38], but chromatin inaccessibility within these regions has not yet been directly measured in filamentous fungi. In Saccharomyces cerevisiae, methylation of H3K36 is mediated by a single histone methyltransferase, SET2, which associates with elongating RNA polymerase to methylate H3K36 in coding sequences [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%